Demonstration of Measurement-Enhanced State Preparation and Erasure Conversion in a Molecular Tweezer Array - Connor M. Holland; Yukai Lu; Samuel J. Li; Callum L. Welsh; Lawrence W. Cheuk (Physical Review X)
Programmable optical tweezer arrays of molecules are an emerging platform for quantum simulation and quantum information science. For these applications, the reduction and mitigation of errors remain major challenges. In this work, we leverage the rich internal structure of molecules to mitigate two types of errors—internal state preparation and qubit leakage errors. First, we demonstrate robust measurement-enhanced tweezer preparation at a record fidelity using site-resolved error detection followed by tweezer movement. Second, using a new hyperfine qubit encoding well suited for use as a quantum memory, we demonstrate site-resolved detection of qubit leakage errors (erasures) induced by blackbody radiation. This approach constitutes the first demonstration of erasure conversion in molecules, a capability that has found recent interest in quantum error correction. Our work opens the door to new possibilities with molecular tweezer arrays: Measurement-enhanced preparation opens access to mesoscopic defect-free molecular arrays that are important for quantum simulation of interacting many-body systems; erasure conversion in molecular arrays lays the technical groundwork for midcircuit detection, an important capability for explorations in quantum information processing.